2020
DOI: 10.1155/2020/7683450
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Study of Medicinal Plants Used by Traditional Healers to Treat Cancer‐Like Symptoms in Eleven Districts, Ethiopia

Abstract: There is no ethnobotanical study conducted specifically on medicinal plants traditionally used to treat cancer in Ethiopia. Yet, traditional herbalists in different parts of the country claim that they have been treating cancer-like symptoms using herbal remedies. The objective of this study was to document medicinal plants traditionally used to treat cancer-like symptoms in eleven districts, Ethiopia. Traditional herbalists were interviewed using semistructured questionnaires, and field visits were also carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 114 publications
(308 reference statements)
3
29
0
Order By: Relevance
“…These studies are in contrast with studies carried out in other regions of the continent [43,44]. In many ethnobotanical studies, the leaf is the most used organ in traditional medicine [46][47][48][49][50], but this study indicates the root as the most used organ (Figure 4) as in surveys of aphrodisiac plants conducted in India [51], Nigeria [25] and Mali [52]. Aside from the fact that the root constitutes a storage organ where several secondary metabolites with various therapeutic properties can be encountered, it symbolizes power, according to the people surveyed.…”
Section: Discussionmentioning
confidence: 93%
“…These studies are in contrast with studies carried out in other regions of the continent [43,44]. In many ethnobotanical studies, the leaf is the most used organ in traditional medicine [46][47][48][49][50], but this study indicates the root as the most used organ (Figure 4) as in surveys of aphrodisiac plants conducted in India [51], Nigeria [25] and Mali [52]. Aside from the fact that the root constitutes a storage organ where several secondary metabolites with various therapeutic properties can be encountered, it symbolizes power, according to the people surveyed.…”
Section: Discussionmentioning
confidence: 93%
“…The use of indigenous plant species to treat a number of ailments such as cancer, toothache and stomach ache in different parts of Ethiopia has been frequently reported [5][6][7]. In addition to the extensive use of enset as human food and animal feed, some enset landraces play a well-known and important role in traditional medicine due to their use in repairing broken bones and fractures, assisting the removal of placental remains following birth or an abortion, and for treatment of liver disease [8][9][10].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, in agreement with the investigation conducted in Ankober district (Lulekal et al, 2013), Kilte Awulaelo District (Teklay et al, 2013), and Libo Kemkem District (Chekole et al, 2015) of Ethiopia, the dominant medicinal plant families documented were Fabaceae, Lamiaceae, Solanaceae, Euphorbiaceae, Asteraceae, and Poaceae. This could be related to the fact that these families are the most prevalent in Ethiopian and Eritrean ora (Tesfaye et al, 2020). Furthermore, recent chemical screening investigations revealed that the greatest number of plant species in these families have bioactive chemicals Leaves are the most used plant part for the preparation of traditional herbal remedies in the study district.…”
Section: Medicinal Plant Species Compositionmentioning
confidence: 95%